Third Order Universal Filter Using Single Operational Transresistance Amplifier - Mourina Ghosh; Sajal K. Paul; Rajiv Kumar Ranjan; Ashish Ranjan (Journal of Engineering, 2013)
This paper proposes a multi-input single-output (MISO) third order voltage mode (VM) universal filter using only one operational transresistance amplifier (OTRA). The proposed circuit realizes low-pass, high-pass, all-pass, band-pass, and notch responses from the same topology. The PSPICE Simulation results using 0.5 μm CMOS technology agree well with the theoretical design.